Analysis of Willingness to Pay (WTP) at Vocational High School - Anik Susanti; Dyah Maya Nihayah (Economics Development Department, Universitas Negeri Semarang, Indonesia, 2019)
The purpose of this study is to estimate and analyze the willingness to pay (willingness to pay) and fax tor the factors that affect the willingness to pay at Vocational High School in the of Semarang. The method used is Contingent Valuation Method (CVM) and multiple linear regression analysis. The number of samples in this study were 100 respondents, the sampling technique was done by purposive sampling and proportional sampling. The results of this study indicate that the average willingness to pay (WTP) of households in Vocational High Schools in Semarang is Rp. 167.950,00. Factors that have a significant influence on WTP values ​​are income variables, number of household dependents, age and length of access. Whereas the factors that have no effect on willingness to pay (WTP) are parents' education variables. Based on the results of the study, the suggestions that can be put forward are the management or the government to improve the quality of the Vocational School as well as the development of a transparency policy on the collection and allocation of user fees and other resources